Trends in incidence and clinical outcomes of Clostridioides difficile infection, Hong Kong - Guo, Cosmos L. T. (2022)
We conducted a territorywide survey to investigate the epidemiology, risk factors, and clinical outcomes of Clostridioides difficile infection (CDI) among hospitalized patients in Hong Kong. A total of 17,105 cases of CDI were identified, of which 15,717 (91.9%) were healthcare-associated and 1,025 (6.0%) were community-associated. Although CDI incidence increased substantially from 2006 to 2017, it plateaued in 2018 and 2019. The 30-day mortality rates decreased from 20.1% in 2015 to 16.8% in 2019, whereas the 60-day recurrence rates remained constant at â‰ˆ11% during the study period. Cross-correlation statistic showed significant correlations between incidence trend and overall antimicrobial drug use (r = 0.865, p<0.001), which has decreased as a result of an antibiotic stewardship program initiated in 2017. Our data suggest a turning point in C. difficile epidemiology that could be related to the changing pattern of antimicrobial drug use.